Implementation of fuzzy analytical hierarchy process on notebook selection - Abadi, Satria; Huda, Miftachul; Basiron, Bushrah; Suhaila Ihwani, Siti; Azmi Jasmi, Kamarul; Hehsan, Aminudin; Safar, Jimaain; Kilani Mohamed, Ahmad; Hassan Wan Embong, Wan; Marzuki Mohamad, Ahmad; Shakib Mohd. Noor, Sulaiman; Novita, Dona; et al. (International Journal of Engineering and Technology, 2018)
Notebooks are technological devices widely adopted to assist in human daily life including learning, business, communication and other tasks. Equipped with the distinctive features, notebook was facilitated more simply for one touch screen basis to enable freely in exploring the usersâ€™ creativity. This study attempts to examine the process of selecting notebook brand among the consumers. Using AHP (Analytical Hierarchy Process) to help decision support system in the selection of Notebook from decision support systems designed to enhance all decision-process through identifying problems, selecting relevant data and defining the approaches was used to evaluate the selection of alternatives in the decision-making process. The finding reveals that the visibility of decision making into the ranking of priority with alternative choice of notebook can be viewed as follows Zyrex 16%, HP 15%, Asus 14%, Apple 13%, Samsung and Axioo 11%, Acer and Toshiba with priority 10 %.Â